The reliability analysis for Malaysian internet and sexual activities inventory and its practical implication - Hawafi, Harisa; Hassan, Siti Aishah; Mohd Ayub, Ahmad Fauzi (Human Resource Management Academic Research Society, 2017)
Despite the increasing number of internet subscribers in Malaysia, parallel with the increment of social issues related with the internet, an established instrument that measure sexual activities and internet that fit with Malaysian sample is crucially needed. Thus, this paper discussed the reliability of Malaysian Internet and Sexual Activities Inventory (MISAI) established by Hassan, Ayob, Talib and Abu Bakar (2013). The MISAI contains 23 items, rated with five-point from “Never true” to “Often true”, with the minimum score of 23 and maximum score of 115. The reliability of the instrument was tested into two sample groups, which are teenager aged 13 to 18 years old and university student aged between 20 to 24 years old. The Cronbach’s Alpha for pre-test for the first group (N=30) is α = .929, where the Cronbach’s Alpha for post-test (N=648) is α = .906. The reliability for the second group (N=30) is α = .834. The results indicate MISAI has high reliability (α> .70) and can be used to measure cybersex involvement among Malaysian sample. Practically, MISAI can be used by the counsellor to identify to what extend the client involved in cybersex activities.